ENHANCING STATE PROPERTY MANAGEMENT IN CARTOGRAPHIC-GEODETIC PRODUCTION - Ergashev , Muslimbek Shuhratjon o‘g‘li (Innovative Development in Educational Activities, 2023)
This research aims to explore strategies for enhancing state property management in cartographic-geodetic production. The study examines the current challenges faced in managing state property and proposes innovative approaches to address these issues. By analyzing the role of cartographic-geodetic production in property management, this research seeks to provide insight into improving efficiency, accuracy, and overall effectiveness in this domain.